Assessment of Land Degradation in Semi-Arid Zone of Central Tanzania - International Institute of Tropical Agriculture; University of Bonn (International Food Policy Research Institute, 2021)
A sub-national field assessment of land degradation was conducted in the Kongwa districts of Tanzania in December 2019. 34 sampling plots were selected using a stratified sampling method based on a land cover map. One site that hosts Africa RISING technologies on land rehabilitation was purposely selected to act as a control. The primary sampling plots measured 100*100m and were subdivided into replicate sub-plots measuring 30x30m. A sub-sample of 3 sub-plots was selected in each primary plot for assessment of land degradation. The observations from 3 subplots (30*30) were averaged to obtain an aggregate value for the larger plot (100x100m). The antecedent biophysical conditions in the sampling plot were recorded i.e. the land use, degree of slope, topographical position, soil color, crop types grown and land tenure. The percentage of area that was undegraded in each plot was also estimated visually. A questionnaire for mapping land degradation and sustainable land management was applied for visual assessment of the type, extent, degree, and direct causes of land degradation. The different types of land degradation, for example erosion by water, were scored whether they are present or not, in addition to their extent and degree (intensity). The extent represented the proportion of a sub-plot covered by different types of land degradation, the degree was divided into 4 classes in ascending order of intensity of land degradation (0 = Light, 1 = Moderate, 2 = Strong, 3 = Severe). Moreover, the type, purpose, extent, and effectiveness of sustainable land management practices (SLM) were visually assessed in every subplot. Data were recorded using the mobile-based KoboCollect toolbox and transmitted to a cloud database for storage and descriptive analysis.